Electrification of Plasma with its Rapid Heating (Global Journal of Science Frontier Research, 2018)
The concept of scalar-vector potential provides for the dependence of electrical pour on the moving charge from its speed. In this concept the charge is not the invariant of speed. Up to now only indirect experiments, connected with the appearance of electric pulse with the space thermonuclear explosions testified in favor indicated concept. In the proposed article are carried out the straight experiments, which attest to the fact that in the process of the warming-up of plasma it acquires unitary charge. These experiments were carried out by the way of the microburst of the thin metallic wires, through which was passed the current from the capacitor bank of great capacity.
Keywords: plasma; scalar-vector potential; faraday's cell; charge; electrization; micro-burst